2015
DOI: 10.1111/cdoe.12148
|View full text |Cite
|
Sign up to set email alerts
|

Income‐related inequality and inequity in the use of dental services in Finland after a major subsidization reform

Abstract: It seems that income-related inequality and inequity in the use of dental services narrowed only temporarily after the reform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 28 publications
1
46
0
4
Order By: Relevance
“…Socioeconomic inequality in the access to dental care services has been confirmed in a number of countries [6,7,8,9,10,11,19,20,21], while the influence of country-specific health insurance systems has also been suggested [8,22,23]. Therefore, we think it would be meaningful and interesting to clarify the impact of SES (socioeconomic status) on the access to dental care services in Japan, where a universal insurance system has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic inequality in the access to dental care services has been confirmed in a number of countries [6,7,8,9,10,11,19,20,21], while the influence of country-specific health insurance systems has also been suggested [8,22,23]. Therefore, we think it would be meaningful and interesting to clarify the impact of SES (socioeconomic status) on the access to dental care services in Japan, where a universal insurance system has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Dental care has important effects on oral health, which is essential to general health and is a determining factor for the quality of life . It has been found that limited access to dental care and economic barriers have strong effects on oral health and its equity . However, pro‐rich inequality in dental care utilization has been found in both developed and developing countries .…”
Section: Introductionmentioning
confidence: 99%
“…Oral health problems are more prevalent in lower social strata, but those with higher incomes and better education use more dental health services . Socioeconomic inequalities in dental care could even have widened in Europe during the global economic crisis which started in 2007.…”
Section: Introductionmentioning
confidence: 99%